DOMINANT HEIGHT GROWTH AND SITE INDEX MODEL FOR TEAK IN GLÓRIA D’OESTE, MATO GROSSO STATE - ZIECH, Beno Guilherme; SILVA, Versides Sebastião de Moraes e; DRESCHER, Ronaldo; VENDRUSCOLO, Diogo Guido Streck (Brazilian Journal of Biometrics, 2017)
The aim of this study was to estimate the local productive capacity of a stand unthinned of Tectona grandis L. f., known as teak, in Glória d’ Oeste, MT, Brazil. The database is from complete stem analysis of 16 dominant trees. To model the dominant height growth of the tree, it was tested three biometric templates, and site classification analysis was conducted by the method of the guided curve. The selection of best model was conducted by using statistical indicators and graphical analysis of residues. The Weibull model showed to be the best model in relation to the others and, from this model, it was created the site index curves and established four productive classes. The teak has adequate production potential for the establishment of stands in the study area, providing 144 months average dominant height of 22.1 m, and in the productive class I, this value may be vary from 25.1 m to 28.1 m.